2007
DOI: 10.1242/jeb.02709
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and acid–base balance in the American lobsterHomarus americanus

Abstract: However, thermal change can alter lobster acid-base status over a time course of minutes. Acute increases in temperature trigger a respiratory compensated metabolic acidosis of the hemolymph. Both the strength and frequency of the lobster heartbeat in vitro are modulated by changes in pH within the physiological range measured in vivo. These observations suggest that changes in acid-base status triggered by thermal variations in the environment might modulate lobster cardiac performance in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Temperature has been shown to be an important determinant of metabolism (Qadri et al . ), behaviour (Crossin et al . ) and several life history traits of this species (Lawton & Lavalli ).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been shown to be an important determinant of metabolism (Qadri et al . ), behaviour (Crossin et al . ) and several life history traits of this species (Lawton & Lavalli ).…”
Section: Introductionmentioning
confidence: 99%
“…Adult lobsters have a thermal preference of ≈16°C (range of 15-18°C), but responses to temperature can change on a seasonal basis because of acclimatization (Worden et al 2006;Qadri et al 2007). Crossin et al (1998) showed that in the summer lobsters avoided water temperatures above 18°C, which were >5°C warmer than the ambient temperature at that time of year.…”
Section: Introductionmentioning
confidence: 99%
“…Acute increases in temperature trigger metabolic acidosis of the hemolymph. Homeostatic mechanisms involve the strength and frequency of the heartbeat that are modulated by changes in pH [39]. These cardiac output variations increase the gill gas exchange efficiency for immersed organisms; respiration compensates for the temperature effect but is likely not to be effective in the case of emersed aquatic organisms where gill ventilation is impaired.…”
Section: Discussionmentioning
confidence: 99%